Massive proliferation of lens epithelial remnants after Nd-YAG laser capsulotomy. Issue 3 (March 1995) - Jones, N P; McLeod, D; Boulton, M E
Abstract : Eight eyes exhibited massive proliferation of lens epithelial remnants following Nd-YAG posterior capsulotomy. All eyes had pre-existing retinal pathology. Six had undergone vitrectomy (four for proliferative diabetic retinopathy) before extracapsular cataract extraction with posterior chamber intraocular lens implantation. The other two eyes had familial exudative vitreoretinopathy or retinopathy of prematurity, respectively. Five eyes required removal of the lens proliferations via a pars plana approach. High levels of growth factors in the posterior segment associated with proliferative disorders of the retina may play a role in lens cell proliferation.